The potential carbon emissions reduction from warehousing activity using vegetation projection planting - Natanael, Joseph (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Large energy consumption and environmental impact from logistical operations which majorly caused by the lighting, heating, cooling, and air conditioning systems alongside fixed and moving material handling equipment are now a major contributor to GHG (Greenhouse Gases). This research objective is to calculate the potential carbon emissions reduction by implementing vegetation projection planting on the company and alternative energy implementation. The method used in this study is by recording and calculating data from the company operational which then convert into data activity. The results from this study stated that company operational contribute 6,588,252.19 KgCO2/month. The existing vegetation capable to absorb 3,810 KgCO2/month, meanwhile the potential carbon emissions reduction which come from planting projection and alternative energy implementation is 6,928,718.7 KgCO2/month. With the increasing of environmental impact from logistical operations, it is necessary to conduct environmental assessment regarding the company business process. Calculating GHG emissions in form of carbon emissions can be the first step to conduct the assessment. Utilization of available green open space area and alternative energy implementation is some potential method to direct or indirectly reduce carbon emissions from warehousing operations.